Effects of Medicago polymorpha L. cover cropping in Sardinia vineyards - Nieddu G.; Graviano O.; Lostia M.; Porqueddu C. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The influence of different soil management systems on vegetative and reproductive grape behaviour and wine quality was studied during 1995-1998 in Sardinia. Cover crop by Medicago polymorpha L., natural herbage covering and the herbicide+tillage technique were evaluated in irrigated vineyard. Natural covering affected grape yield and wine quality negatively. M. polymorpha established very well and showed satisfactory autumn re-establishment in the second and third years whereas burr medic covering decreased year by year. Differences in the occurrence of phenological phases were observed between vine and burr medic with no competition during the reproductive of the grape. Cover crop by burr medic determined vine vegetative and productive performance similar to that produced by the traditional management treatment and M. polymorpha induced better wine quality.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)